Recognizing cited facts and principles in legal judgements - Adam Wyner (Artificial Intelligence and Law, 2017)
In common law, lawyers cite facts and legal principles from precedent cases for their arguments in support of their current case. Such facts and principles must be identified, though this is a highly time intensive task. We demonstrate that human annotators can agreement on which sentences are facts or principles. A supervised machine learning framework can automatically annotate sentences containing such legal facts and principles based on linguistic features, reporting precision and recall figures of between 0.79 and 0.89 using a Bayesian classifier.